FILSAFAT HUKUM ISLAM SEBAGAI LANDASAN EPISTEMOLOGIS STUDI HUKUM HOLISTIK - Nasywa Kamilah; Muhammad Jaidi (Yayasan Baitul Hikmah al-Zain, 2025)
This study explores the philosophical foundations of Islamic law to address contemporary epistemic crises caused by secularization and legal positivism, particularly in Indonesia’s pluralistic context. Through a qualitative-philosophical design, it analyzes six integrated epistemological pillars Al-Ghazali’s synthesis of revelation-reason-morality, al-Shāṭibī’s maqāṣid al-sharīʿah, Harun Nasution’s transcendent-empirical bridge, Juhaya S. Praja’s contextual dialectics, critique of Kelsen’s legal positivism, and multidisciplinary integration to reconstruct a holistic Islamic legal philosophy that unites kauliyah (scriptural values) and kauniyah (empirical sciences). Findings reveal that reducing Islamic law to formalistic rules ignores its transformative, ethical, and contextual essence. The proposed framework not only counters Western positivist limitations but also provides an epistemological basis for expanding Islamic law beyond marriage and banking into socio-environmental-economic domains such as climate justice, inclusive economics, and minority rights. While normative and non-empirical, this model offers a robust foundation for future participatory policy development among ulama, scholars, and state actors.